الطب الشعبي والطب العلمي : دراسة وصفية تحليلية - المشهداني، عبدالفتاح محمد (جامعة الموصل - مركز دراسات الموصل, 2011)
أن الاهتمام بدراسة الطب الشعبي، ليس مجـرد قـضية علميـة تـستحق الاهتمام لكنه أيضا قضية مجتمعية تستحق التوقف عندها، لأنها أصبحت محـط اهتمام العديد من المجتمعات والثقافات. \ لقد أثبتت الدراسات الحديثة في الطب الشعبي أن الصراع بينـه وبـين الطب الحديث، هو صراع متصل لم يتوقف بالرغم من الإنجازات العلمية فـي مجال الطب العلمي الحديث. فالطب العلمي الحديث ينظر إلى المرض على انه نتيجة لبعض الأسباب الفسيولوجية أو بفعل عوامل خارجيـة مثـل الجـراثيم والميكروبات. بينما الطب الشعبي يرجع أسباب المرض إلى عوامـل أخرى، فهو ينظر إلى جسم الأنسان على انه وحدة متكاملة لامجال للفصل بين عـضو وآخر، لكن الطب الحديث يفصل بين أعضاء جسم الأنسان من خلال التطـور العلمي والتخصصات العلمية المتنوعة، فأصبح لكل عضو من أعضاء جـسم الأنسان طبيباً خاصاً فهو يهتم بعلاج المرض اكثر من اهتمامه بعلاج المريض. \ تضمن البحث ثلاث مباحث أساسية، تنـاول المبحـث الأول الجـذور التاريخية للطب الشعبي، أما المبحث الثاني فانه يتحدث عن الصلات بين الطب الشعبي والطب العلمي، وركز المبحث الثالث على مستقبل الطب الـشعبي فـي مواجهة التطور الهائل للطب الحديث إضافة إلى مقدمة، وأهمية وأهداف البحث التي تحاول تشخيص طبيعة العلاقة بين الطب الشعبي والطب العلمي، وهل هي علاقة تضاد وتنافر أم علاقة تقارب وتكامل؟ The concern of studing Folk medicine is not more ascientifical matter deserves ones to interest, but also it is societal matter need from us to stop on it ,because it becomes asubject concerning with societies and cultures. The recent studies in the field of folk medicine have been shown that the conflict between Folk medicine and scientific medicine is still continuous ,inspite of the progress and scientifical achievements in the field of medicine.The modern medicine look at disease as a result of physical and pathological causes.or under the effect of some bacterias and microbes. while,the factors of disease according to folk medicine is due to the other factors and look at the human body as acomplete unit not possible to separate from one part to others, while the scientific medicine study the human body through scientifical and technical specialization and the doctors take into consideration the diseases more them the patients.The research contained the diseases, the first one try to search in the historian roots of folk medicine, but the chapter two study the corolation between the folk medicine and scientific medicine, whisper the third chapter concentrate on the future of folk medicine in facing the huge development in the field of modern medicine. The research also try to threw some questions about the natural of relations between folk medicine and scientific medicine, wheather such relation is negative or positives.
Keywords: الطب الشعبي -- الطب العلمي -- وسائل العلاج -- الأطباء -- الأمراض